Can anyone explain how to solve base 60 problems. All I know is my sister came home and asked. here's what she gave me. a*b=[(ab)(ab)]/4-[(a-b)(a-b)]/4 Anyone make any sense out of it.
Follow Math Help Forum on Facebook and Google+
anyone?
Originally Posted by mcdanielnc89 Can anyone explain how to solve base 60 problems. All I know is my sister came home and asked. here's what she gave me. a*b=[(ab)(ab)]/4-[(a-b)(a-b)]/4 Anyone make any sense out of it. Just expand it $\displaystyle \frac{(a+b)^2}{4}-\frac{(a-b)^2}{4}=\frac{1}{4}\left((a+b)+(a-b)\right)\left((a+b)-(a-b)\right)=\frac{ab}{4}\cdot{4}=ab$
View Tag Cloud